EFECTO DE LA GnRH SOBRE LAS CARACTERÍSTICAS SEMINALES Y TESTOSTERONA SÉRICA EN ALPACAS - Pacheco Curie, Joel I.; Huanca Mamani, Teodosio; Santiani Acosta, Alexei; Evangelista Vargas, Shirley; Mamani Cato, Rubén Herberht; Quispe, T. L. (Universidad Nacional del Altiplano - Puno, 2021)
4 páginas